2019
DOI: 10.1038/s41467-019-12842-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial MgrB peptide activates chemoreceptor Fpr3 in mouse accessory olfactory system and drives avoidance behaviour

Abstract: Innate immune chemoreceptors of the formyl peptide receptor (Fpr) family are expressed by vomeronasal sensory neurons (VSNs) in the accessory olfactory system. Their biological function and coding mechanisms remain unknown. We show that mouse Fpr3 (Fpr-rs1) recognizes the core peptide motif f-MKKFRW that is predominantly present in the signal sequence of the bacterial protein MgrB, a highly conserved regulator of virulence and antibiotic resistance in Enterobacteriaceae. MgrB peptide can be produced and secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 85 publications
(137 reference statements)
0
44
0
Order By: Relevance
“…The vomeronasal organ (VNO) specialises in detecting pheromones for the purpose of reproductive behaviours such as maternal aggression and sexual attraction 5 . The VNS is also involved in the recognition of major histocompatibility complex (MHC) associated peptides 6 , kairomones 7 and aversive molecules 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The vomeronasal organ (VNO) specialises in detecting pheromones for the purpose of reproductive behaviours such as maternal aggression and sexual attraction 5 . The VNS is also involved in the recognition of major histocompatibility complex (MHC) associated peptides 6 , kairomones 7 and aversive molecules 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The agonist potential of formylated peptides was extensively tested for the mouse FPR-rs1 in a heterologous expression assay, revealing that FPR-rs1 responds to some formylated bacterial signal peptides, but this vomeronasal receptor appears more narrowly tuned than immune FPRs. Recently, it was shown that HEK293T cells expressing FPR-rs1 respond to the formylated peptide motif f-MKKFRW (Bufe et al 2019 ), a signal peptide present in membrane proteins of a large family of Gram-negative bacteria, the Enterobacteriaceae (which include Escherichia , Salmonella , and Shigella , as well as a few Gram-positive bacteria). More specifically, the MKKFRW motif is highly conserved at the N-terminus of the virulence-regulating factor protein MgrB of these bacteria.…”
Section: Function Of Vomeronasal Fprsmentioning
confidence: 99%
“…Mice lacking the FPR-rs1 receptor or components of the vomeronasal signaling cascade do not display any avoidance of the MgrB formylated peptide, clearly suggesting a critical role for FPR-rs1 as a chemoreceptor involved in the behavioral response to bacterial cues (Fig. 2 ) (Bufe et al 2019 ).…”
Section: Function Of Vomeronasal Fprsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice vomeronasal sensory neurons ((VSNrs) detect non-volatile chemostimuli that are indicative of infection and health status, immunological fitness, and genetic compatibility ( Boillat et al, 2015 ). The VSNrs include formyl peptide chemoreceptors that respond to specific bacterial cues as well as other receptors and mechanisms for detecting bacterial toxins, quorum-sensing molecules, and lipopolysaccharides ( Bufe et al, 2019 ; Chiu et al, 2013 ). Less is known regarding the detection of non-volatile viral associated cues.…”
Section: Olfactory Mechanismsmentioning
confidence: 99%